A Versatile Tumor Microenvironment-Responsive Nanoprobe for Cancer Screening and Early Detection - Fangyan Ouyang; Huihuang Xiong; Dan Ding; Yiqun Wan; Minhai Liu; Yongye Liang; Hongjie Dai; Hao Wan (Journal of the American Chemical Society, 2026)
Abstract It has been highly challenging to reliably detect various cancers at an early stage when tumors are just millimeters in size. To address this, we developed a tumor microenvironment (TME)-responsive nanoprobe, PR-KAd@CD-AuNC, enabling cross-validated cancer detection through in vivo second near-infrared (NIR-II) fluorescence imaging and in vitro colorimetric urinalysis. The nanoprobe consists of three integrated components: a renal-clearable signal-output segment (cyclodextrin-functionalized gold nanocluster, CD-AuNC), a tumor-targeting and size-controlling component (PR), and a matrix metalloproteinase-2 (MMP2)-cleavable linker (KAd). PR, composed of 8-arm poly(ethylene glycol) for prolonged circulation and c(RGDfK) peptides for αvβ3 integrin targeting, directed selective tumor accumulation after intravenous injection of PR-KAd@CD-AuNC. The intrinsic emission of CD-AuNC above 1100 nm enabled high-resolution, real-time NIR-II fluorescence imaging with attenuated photon scattering, allowing precise tumor delineation. Within the TME, specifically overexpressed MMP2 cleaved the KAd linker, releasing ∼2 nm CD-AuNC fragments from the ∼10 nm parent nanoprobe. Being smaller than the ∼5.5 nm renal filtration threshold, these fragments were renally excreted. Concurrently, the peroxidase-like activity of CD-AuNC catalyzed tetramethylbenzidine oxidation to produce a visible blue signal, providing a simple and low-cost urinalysis method suitable for broad cancer screening applications. This dual-modality strategy effectively distinguished cancers from inflammation and other diseases, detecting small tumors for multiple cancer types with a sensitivity surpassing that of computed tomography (CT) imaging, which makes it a promising early detection approach. Furthermore, it was also employed to dynamically assess cancer therapeutic efficacy (i.e., immunotherapy, chemotherapy, and surgical resection), suggesting clinical value for guiding treatment decisions.